Model for Ulayat Land Dispute Resolution Based on Participatory Justice in the Era of Sustainable Development - B Rini Heryanti; Amri Panahatan Sihotang (Universitas Negeri Semarang, 2022)
The goal of this research is twofold: to investigate and evaluate the existing model for the resolution of disputes concerning customary rights in Indonesia and to devise a model for the resolution of such conflicts that is founded on participatory justice and is appropriate for use in an era in which sustainable development is a priority. The Juridical Empirical approach is employed as the methodology for this investigation. According to the study’s findings, the lack of instruments or mechanisms for resolving ulayat land disputes will make it difficult for indigenous peoples to gain access to the magical religious values of indigenous peoples related to the spiritual, social, and cultural values of indigenous peoples. These magical religious values are tied to indigenous peoples’ traditional ways of life. Indigenous peoples’ rights can be protected through participatory justice by exerting influence over the processes and policies involved in the resolution of ulayat land disputes. This ensures that indigenous peoples will continue to have access to social rights and human rights about preserving their values, spiritual, social, and cultural qualities sustainably.